Nők az iskolapadban - Bojer Anasztázia (2015)
To be woman or man - this is an important determining factor - of our social existence. There were mentionable changes during the last 150 years, if we take the social expecta-tions concerning to women and men, also their cue in the family and society both. There were not the same rules for girls and boys in schools when the education became compul-sory in our country that is why there was a notable variance in the qualification of one an-other. The official policy of education focused exclusively only for boys. For girls earlier the most important was to be married and to give a birth a child. Fortunately we always had citizens fighting against this inequality. The main aim of this paper is to review the struggle concerning women’s education through the main social and economic tendencies, giving the chance for women to be edu-cated as men on the elementary, secondary and also on tertiary education levels. Statistical data is being used to demonstrate the changes of school qualification of the two genders. In this paper the history of the women’s education is only focused on the acts of the official school-system, except for necessary mentioning of other types of training (e. g. courses). Tables and diagrams are using the data of the official population censuses, this is the only survey checking the level of the education concerning to all of the citizens. Moreover the story of Vilma Hugonnai is written, who wanted to naturalize her di-ploma on human medical sciences in order to may help patients in the country where she was born. Only to find this took 18 years due to the hidebound opinion of politicians about women. To recap the substance, in the beginning of the 20th century it was almost impossi-ble for a woman to graduate a university of medicine and get a diploma there. Thanks to the people who contested decades, nowadays the education of women is completely ac-cepted. Women taking part in the elementary, high school and tertiary education have pro-gressively closed up, demonstrating they are able to acquire the same knowledge as men.